IMPORTANCE OF MARKETING IN BUSINESS - Yandasheva Nozanin (American Journals, 2023)
This scientific article describes the ways of organizing marketing activities in business. Marketing services operating in enterprises of different sectors differ from each other in the principles and forms of organization. Most of the literature mentions five principles of organizing marketing services and two forms of its management.
Keywords: business, business entities, marketing, enterprise, market, product, functional-product, functional-market, product.